Exploring entrepreneurial orientation and intentions among technical university students: Role of contextual antecedents. Issue 6 (15th July 2019) - Sahoo, Swagatika; Panda, Rajeev Kumar
Abstract : Purpose: The purpose of this paper is to empirically investigate the impact of the contextual antecedents on the individual entrepreneurial orientation (IEO) of university graduates, which, in turn, affects their entrepreneurial intentions (EIs). Design/methodology/approach: Primary data were collected in the form of 510 valid responses from engineering students across two technical universities in India, through a structured questionnaire consisting of scales adapted from the extant literature, and the data were empirically validated in this study. The reliability and validity measures of the constructs were validated through the confirmatory factor analysis, and the proposed hypotheses were validated using structural equation modelling. Findings: The results of this empirical analysis validate that the contextual antecedents have a significant positive impact on students' entrepreneurial orientation (EO), which, in turn, has a significant positive influence on EIs. Research limitations/implications: This analysis depicts the significance of EO as a perceptual driver at the individual level and substantiates that the availability of resources such as startup capital, access to business information, social networks and supportive university context significantly affects the decision-making process of an individual to venture into an otherwise uncertain occupation of entrepreneurship. Practical implications: The study has the likely potential to help university administrators and policymakers to allocate resources, develop strategies and provide effective entrepreneurial learning in entrepreneurship-oriented courses aimed at honing entrepreneurial skills and self-confidence of the university students. This holistic model can be used as a tool for resource planning and prioritising in order to provide the desired contextual support essential for fostering the IEO of the university students towards adopting entrepreneurial career, thereby assisting them to achieve their career goals and the broader objective of nation-building. Originality/value: This study adopts an innovative approach to empirically validate the EO construct at the individual level, which has been studied at the organisation (firm) level till today. This research explores the relevant contextual antecedents and analyses their impact on IEO as well as the explanatory capacity of IEO to explain students' EIs in the contextual backdrop of universities in a fast transitioning economy like India.